2008
DOI: 10.1158/0008-5472.can-06-4497
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Is the Principal Pathway for the Repair of DNA Damage Induced by Tirapazamine in Mammalian Cells

Abstract: Tirapazamine (3-amino-1,2,4-benzotriazine-1,4-dioxide) is a promising hypoxia-selective cytotoxin that has shown significant activity in advanced clinical trials in combination with radiotherapy and cisplatin. The current study aimed to advance our understanding of tirapazamine-induced lesions and the pathways involved in their repair. We show that homologous recombination plays a critical role in repair of tirapazamine-induced damage because cells defective in homologous recombination proteins XRCC2, XRCC3, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 41 publications
(43 reference statements)
2
49
0
Order By: Relevance
“…6B), agrees with cell culture data in the present and previous studies (30,32) and suggests that the benzotriazine di-N-oxide class is less suited than cross-linkers to exploiting this target. The latter may reflect the lesser dependence on HR for resolution of lesions induced by SN30000 under hypoxic conditions, and cell entrapment of the cytotoxic-free radical metabolites of SN30000 precluding efficient bystander effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6B), agrees with cell culture data in the present and previous studies (30,32) and suggests that the benzotriazine di-N-oxide class is less suited than cross-linkers to exploiting this target. The latter may reflect the lesser dependence on HR for resolution of lesions induced by SN30000 under hypoxic conditions, and cell entrapment of the cytotoxic-free radical metabolites of SN30000 precluding efficient bystander effects.…”
Section: Discussionsupporting
confidence: 90%
“…By deploying in vitro isogenic models, we (30,31) and others (26,32) have demonstrated that several HAP are capable of exploiting HR defects analogous to those frequently observed in TNBC (8,10). A comparison of chemical classes in Rad51d-knockout Chinese hamster cells suggested that the DNA cross-linking HAP (TH-302 and PR-104) may have greater selectivity for HR dysfunction than benzotriazine-di-N-oxides or nitroCBI (30).…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, using one of the same pairs of lines (AA8 and irs1SF), Evans and colleagues observed a 4Â enhanced potency of tirapazamine in the irs1SF compared with the wild-type whereas we observed a 50Â enhancement with TH-302. This difference is consistent with the activity of TH-302 being more specific to the HDR mechanism of action as tirapazamine was shown to also yield lesion repair by BER (13). The findings that TH-302 activity is enhanced in the context of HDR repair pathways is of particular note because of the recent finding that hypoxia results in decreased expression of homologous recombination proteins, including XRCC-3, (the protein mutated in the irs1SF line), BRCA1, as well as other HDR-related genes (42)(43)(44).…”
supporting
confidence: 80%
“…DNA repair mutant Chinese hamster ovary (CHO) cell lines were provided by Martin Brown (Stanford University, Stanford, CA; ref. 13). The UWB1.289 pair was from Elizabeth Swisher (University of Washington, Seattle, WA), the VC-8 pair was from Graeme Smith (KuDOS), and the FANCA pair was from Sara Rockwell (Yale University, New Haven, CT).…”
Section: Cell Linesmentioning
confidence: 99%
“…The hypoxic selectivity of tirapazamine is due to the rapid reoxidation of the initial radical to the parent prodrug by O 2 . Thus, tirapazamine functions as a hypoxia-activated agent (20,21), exhibiting the capability of potentiating the antitumor efficacy of many anticancer drugs (22)(23)(24)(25). The putative mechanism may be attributed to its suppression of the accumulation of HIF-1a protein.…”
Section: Introductionmentioning
confidence: 99%